Distribution and biogeographic trends of decapod assemblages from Galicia Bank (NE Atlantic) with connexions with different water masses - Cartes, Joan Enric; Papiol, Vanesa; Valeiras, J.; Frutos, I.; Macpherson, Enrique; Punzón, Antonio; Serrano, Alberto (2012)
XIII International Symposium on Oceanography of the Bay of Biscay. ISOBAY 13, 11-13 April 2012, Santander, Spain Three cruises were performed on the Galicia Bank (NW Iberian Peninsula, NE Atlantic) in 2009 (Ecomarg0709), 2010 (BanGal0810) and 2011 (BanGal0811) during July–August (project INDEMARES). Decapods and other macrobenthic crustaceans (eucarids and some peracarids) were collected with beam trawls (10 mm of mesh size at codend) and a GOC73 otter trawl (20 mm mesh size). 67 species of decapod crustaceans, 6 euphausiids, 19 peracarids and 1 ostracod were collected at depths between 744 and 1808 m. We found 2 new species, the Galatheidae Uroptychus cartesi and the Petalophthalmidae (Mysida) Petalophthalmus sp.1 (under description) and a number of new species for European or Iberian waters. The analysis of assemblages evidenced generalized species renewal with depth, with two different assemblages distributed between 744–ca.1400 m (the seamount top assemblage, STA) and between ca.1500–1800 m (the deep-slope assemblage over seamount flanks, DSA), respectively associated to Mediterranean outflow waters (MOW) and the Labrador Sea Water (LSW). Other significant factor splitting different assemblages over Galicia Bank was the co-occurrence of corals (both colonies of hard corals and/or gorgonians) in hauls. Galatheids (Uroptychus spp., Munidopsis spp.), with Chyrostilids and the Homolodromiidae Dicranodromia mahieuxii formed part of this coral-associated assemblage. Dominant species at the STA were the pandalid Plesionika martia (dominant in intermediate waters in the Mediterranean) and the crabs Bathynectes maravigna and Polybius henslowii, while dominant species at the DSA were of northern origin, the lithodid Neolithodes grimaldii and the crangonid Glyphocrangon longirostris associated to LSW. The diversity (H and J) of small crustaceans collected with beam trawls was controlled by Chl a blooms over bank 3 months before samplings, both at top (Spearman r=0.57, p=0.03) and flanks (r=0.74, p=0.02), while no ...